2023
DOI: 10.1111/php.13832
|View full text |Cite
|
Sign up to set email alerts
|

The photophysics of protonated cytidine and hemiprotonated cytidine base pair: A computational study

Abstract: We here study the effect that a lowering of the pH has on the excited state processes of cytidine and a cytidine/cytidine pair in solution, by integrating time‐dependent density functional theory and CASSCF/CASPT2 calculations, and including solvent by a mixed discrete/continuum model. Our calculations reproduce the effect of protonation at N3 on the steady‐state infrared and absorption spectra of a protonated cytidine (CH+), and predict that an easily accessible non‐radiative deactivation route exists for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…This crossing region, which allowed a fast GS recovery, was separated by a very small energy barrier (<0.1 eV) from CH -min*. This could be reached by the out-of-plane motion of the C5′-H5’ moiety, confirming the indications obtained in our study of hemiprotonated (CH·C) pairs [ 67 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This crossing region, which allowed a fast GS recovery, was separated by a very small energy barrier (<0.1 eV) from CH -min*. This could be reached by the out-of-plane motion of the C5′-H5’ moiety, confirming the indications obtained in our study of hemiprotonated (CH·C) pairs [ 67 ].…”
Section: Resultssupporting
confidence: 88%
“…As discussed in detail in ref. [ 67 ], the lowest-energy bright excited state in (CH·C) is a transition localized on the CH base, mostly involving the C5=C6 double bond. In the following, we label this kind of excited state as CH - .…”
Section: Resultsmentioning
confidence: 99%
“…10,41,42 In light of this, 1mCyt might be considered a useful model compound for eliminating the various tautomeric forms (except for the keto form) in the study of the Cyt excited states 44,45 and to reduce the computational cost in the theoretical exploration of the mechanistic details of the dCyd and Cyd deactivation. 2,3 On the other hand, the precise time constants of the S 1 pp* decay from its PES minimum (t 2 ) and the decay of np* (t 3 ) in 1mCyt are noticeably different from those in Cyt, dCyd and Cyd. 2,10 As shown in Table 1, the value of t 2 is B0.76 ps for This journal is © the Owner Societies 2024 1mCyt in water, which is smaller than the time constant of B1.5 ps for Cyt (Fig.…”
Section: B Comparison Of the Deactivation Dynamics Of 1mcyt With Cyt ...mentioning
confidence: 98%
“…1 1mCyt is also a model compound used in highlevel quantum mechanical calculations for decreasing the computational cost in analyzing the highly complex excited state potential energy surfaces (PESs) and deactivation dynamics of cytidine (Cyd) and deoxycytidine (dCyd) (Scheme 1). 2,3 There is, however, very limited experimental study regarding excited states of 1mCyt, with only one known investigation using time-resolved IR (TRIR) by Keane et al. 4 This study reported that both 1mCyt and Cyt, after photo-excitation, exhibit ultrafast decay from their light-absorbing pp* state with no significant involvement of the np* natured state.…”
Section: Introductionmentioning
confidence: 99%
“…2,[11][12][13][14][15] Considering the complexity of DNA structures, it is attractive to study the photochemical and photophysical properties of larger building blocks of DNAs, such as nucleosides, for understanding the photostability of DNAs in a ''bottom to top'' research scheme. Despite a number of theoretical [16][17][18][19][20][21][22][23] and experimental studies 1,[24][25][26][27][28][29][30][31][32][33][34][35] that have been carried out, the deactivation mechanism of Cyd is still a heated debate. Timeresolved IR spectroscopy experiments observed three decay channels with a sub-picosecond (B0.2 ps), a picosecond (B1.5 ps), and a long (tens to hundreds ps) lifetime of Cyd system in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%